Down among the dead men [large type] : a Peter Diamond investigation - Lovesey, Peter (Lovesey, Peter. Peter Diamond mystery., 2015)
Detective Peter Diamond, who is in Sussex on a Home Office internal investigation, becomes interested in the disappearance of a widely disliked art teacher from a posh private girls' school. Have he and his hapless supervisor stumbled into a web of related crimes?